Quality indicators in breast cancer care: An update from the EUSOMA working group. (November 2017) - Biganzoli, Laura; Marotti, Lorenza; Hart, Christopher D.; Cataliotti, Luigi; Cutuli, Bruno; Kühn, Thorsten; Mansel, Robert E.; Ponti, Antonio; Poortmans, Philip; Regitnig, Peter; van der Hage, Jos A.; Wengström, Yvonne; et al.
Abstract: In 2010, EUSOMA published a position paper, describing a set of benchmark quality indicators (QIs) that could be adopted by breast centres to allow standardised auditing and quality assurance and to establish an agreed minimum standard of care. Towards the end of 2014, EUSOMA decided to update the paper on QIs to consider and incorporate new scientific knowledge in the field. Several new QIs have been included to address the need for improved follow-up care of patients following primary treatments. With regard to the management of elderly patients, considering the complexity, the expert group decided that, for some specific quality indicators, if centres fail to meet the minimum standard, older patients will be excluded from analysis, provided that reasons for non-adherence to the QI are specified in the clinical chart and are identified at the review of the clinical records. In this way, high standards are promoted, but centres are able to identify and account for the effect of non-standard treatment in the elderly. In the paper, there is no QI for outcome measurements, such as relapse rate or overall survival. However, it is hoped that this will be developed in time as the databases mature and user experience increases. All breast centres are required to record outcome data as accurately and comprehensively as possible to allow this to occur. In the paper, different initiatives undertaken at international and national level to audit quality of care through a set of QIs have been mentioned.